Homozygosity for alanine in the mitochondrial targeting sequence of superoxide dismutase and risk for severe alcoholic liver disease - Degoul, F; Sutton, A; Mansouri, A; Cepanec, C; Degott, C; Fromenty, B; Beaugrand, M; Valla, D; Pessayre, D (Gastroenterology (New York, N.Y. 1943), 2001)
For similar ethanol consumption, some subjects only develop macrovacuolar steatosis whereas others develop severe liver lesions. A genetic dimorphism encodes for either alanine or valine in the mitochondrial targeting sequence of manganese superoxide dismutase and could modulate its mitochondrial import. The DNA of 71 white patients with alcoholic liver disease and 79 white blood donors was amplified and genotyped. The frequency of the alanine-encoding allele and the percentage of alanine homozygotes were higher in all patients than in controls and increased with the severity of liver lesions. The percentage of alanine homozygotes was 19% in controls, 17% in alcoholic patients with macrovacuolar steatosis, 43% in patients with microvesicular steatosis, 58% in patients with alcoholic hepatitis, and 69% in patients with cirrhosis. Alcohol consumption in alcoholics was similar whatever the genotype. Alanine homozygosity did not change the risk of developing macrovacuolar steatosis in alcoholics, but increased by 3-fold that of microvesicular steatosis, and 6- and 10-fold that of alcoholic hepatitis and cirrhosis. Homozygosity for alanine in the mitochondrial targeting sequence of manganese superoxide does not modify alcohol consumption and the risk of macrovacuolar steatosis in alcoholics but is a major risk factor for severe alcoholic liver disease.